Frekuensi Radio Identifikasi - Kamal Adzham, Ahmad Nizar (Universiti Sains Malaysia, 2005)
Radio Frequency Identification or RFID is a new technology and building its reputation rapidly. This system is widely use in our daily lives. For an example is ‘Smart Tag’ lane on high ways. The gate automatically opens during the entry of our vehicle. Another example of RFID system is security alarm at shops entrance. The entire product is label with tag and the alarm would be triggered if the product is stolen or brought out passing through the doors. The main objective of this project is to write a program for the microcontroller for the RFID reader so that it could be use for personal purpose, but because it is hard to purchase the tag a 1-bit RFID circuit is designed to give a basic overview on how RFID works. The reader circuit and the tag is said to be resonating at a specific frequency. In industry the frequency that is used is 125 kHz and 13.56 MHz. But in this project the frequency used is 1MHz because of the capability of the equipment (audio generator) used in this project. One of the main problems faced during the development of this project is tuning the antenna to resonant at 1MHz. This is solved easily by using Network Analyzer. For the future student who intent to continue this project could improve the memory of the tag and the reading distance of the tag so that the RFID technology could be improve to a whole new level.